Connecting energy availability and iron deficiency with bone health: Implications for the female athlete - Goldstein, E. R.; Fukuda, D. H. (Strength and Conditioning Journal, 2020)
An inability to meet the energy demands of sport and support physiological functioning can be the result of chronic energy deficiency. Resting energy expenditure, endocrine disruption, menstrual disturbances, and poor bone health are outcomes of low energy availability (LEA). Iron deficiency (ID) can be an outcome of inadequate intake as well as hepcidin activity and its role in the development of exercise-associated ID and anemia. The purpose of this article is to discuss the effects of ID and anemia in combination with LEA and the implications for a female athlete's bone health.